Osmoprotectants play a major role in the Portulaca oleracea resistance to high levels of salinity stress—insights from a metabolomics and proteomics integrated approach - Rodrigues Neto, Jorge Candido; Salgado, Fernanda Ferreira; Braga, Ítalo de Oliveira; Carvalho da Silva, Thalliton Luiz; Belo Silva, Vivianny Nayse; Leão, André Pereira; Ribeiro, José Antônio de Aquino; Abdelnur, Patrícia Verardi; Valadares, Leonardo Fonseca; de Sousa, Carlos Antônio Ferreira; Souza Júnior, Manoel Teixeira (Frontiers in Plant Science, 2023)
Purslane (Portulaca oleracea L.) is a non-conventional food plant used extensively in folk medicine and classified as a multipurpose plant species, serving as a source of features of direct importance to the agricultural and agri-industrial sectors. This species is considered a suitable model to study the mechanisms behind resistance to several abiotic stresses - including salinity. The present study is a second step in building a robust database on the morpho-physiological and molecular responses purslane to salinity stress and its subsequent use in attempting to decode the genetics behind its resistance to this abiotic stress. Here it is presented the characterization of the morpho-physiological responses of adult purslane plants to salinity stress and a metabolomics and proteomics integrative approach to study the changes at the molecular level in their leaves and roots. Crystal-like structures, constituted mainly by Na+, Cl−, and K+, were found in the leaf veins and intercellular space near the stoma, indicating that this species has a mechanism of salt exclusion operating on the leaves, which has its role in salt tolerance. The MOI approach showed that 41 metabolites were statistically significant on the leaves and 65 metabolites on the roots of adult purslane plants. The combination of the mummichog algorithm and metabolomics database comparison revealed that the Glycine, serine and threonine, Amino sugar and nucleotide sugar, and Glycolysis / Gluconeogenesis pathways were the most significantly enriched pathways when considering the total number of occurrences in the leaves - with 14, 13, and 13, respectively - and roots - all with eight - of adult plants; and that purslane plants employ the adaptive mechanism of osmoprotection to mitigate the negative effect of very high levels of salinity stress; and that this mechanism is prevalent in the leaves.